Photoluminescence of ortho-bromobenzophenone: Molecular Solids - Avdeenko, A.A.; Pyshkin, O.S.; Eremenko, V.V.; Strzhemechny, M.A.; Buravtseva, L.M.; Romashkin, R.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
Phosphorescence spectra of crystalline ortho-bromobenzophenone (2-bromobenzophenone, 2BrBP) were measured from 1.6 K to room temperature. A cardinal emission mechanism crossover occurs within this temperature range. At low temperature the phosphorescence spectrum is a superposition of two similar sets of equidistant bands spaced by the C=O stretch frequency. We ascribe these two sets to the emission of two different conformers, one of which is metastable and do not manifest itself above approximately 70 K. Presence of two conformers is explained by thefact that the 2BrBP molecule deforms considerably upon excitation. The emission from the stable conformer survives up to approximately 140 K or even higher. At roughly 60 K and higher, another type of emission reveals itself in the shape of a two very broad partly overlapping bands, which gains in intensity with increasing temperature. Above 150 K only this two-hump feature is observed in phosphorescence spectra. Additional phosphorescence experiments were carried out toelucidate the nature of this spectrum, including phosphorescence measurements of 2BrBP in ethanol solutions as well as time-resolved and varying-xcitation-intensity measurements from crystals. Based on results of all the experiments reported here and on our own single-crystal x-ray structure data we conclude that the above two-band spectrum recorded near room temperature is due to the emission of single-photon bimolecular triplet excimer formed by the carbonyl groups of two neighbor 2-bromobenzophenone molecules. It is got the first time that a bimolecular excimer has been observed and reliably identified in a benzophenone derivative solid.